Evaluation of Teriparatide for Treatment of Osteoporosis in Four Patients with Cystic Fibrosis: A Case Series. (6th March 2014) - Siwamogsatham, Oranan; Stephens, Kelly; Tangpricha, Vin
Abstract : Introduction. Bone disease is a common complication of cystic fibrosis (CF). To date, there have been no reports on the effectiveness of teriparatide, recombinant human parathyroid hormone, to treat CF-related bone disease. Case Presentation. We report on four patients with CF-related bone disease who were treated with teriparatide. Three patients completed two years of therapy with teriparatide, and all had significant improvements in their bone mineral density (BMD). One patient was unable to tolerate teriparatide and discontinued treatment 1 week into therapy. Conclusion. Teriparatide may be a potential treatment option for CF-related bone disease. This report highlights the need for further investigation into the use of teripartide in the CF population.